5x53-{4x[5+(a-2)x7]:3}x6=1
Răspunsuri la întrebare
Răspuns de
5
5x53 - ( 4x(5+(a-2)x7):3)x6=1
265 - (4x(5+(a-2)x7):3)x6=1
(4x(5+(a-2)x7):3)x6=265-1
(4x(5+(a-2)x7):3)x6=264
4x(5+(a-2)x7):3=264:6
4x(5+(a-2)x7):3=44
(5+(a-2)x7):3=44:4
(5+(a-2)x7):3=11
5+(a-2)x7=11x3
5+(a-2)x7=33
(a-2)x7=33-5
(a-2)x7=28
a-2=28:7
a-2=4
a=4+2
a=6
265 - (4x(5+(a-2)x7):3)x6=1
(4x(5+(a-2)x7):3)x6=265-1
(4x(5+(a-2)x7):3)x6=264
4x(5+(a-2)x7):3=264:6
4x(5+(a-2)x7):3=44
(5+(a-2)x7):3=44:4
(5+(a-2)x7):3=11
5+(a-2)x7=11x3
5+(a-2)x7=33
(a-2)x7=33-5
(a-2)x7=28
a-2=28:7
a-2=4
a=4+2
a=6
zgatiuta:
multumesc f mult
Alte întrebări interesante
Limba română,
8 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă